Relationships between athletic ability and academic performance in primary school students: A 3-year follow-up study - Hao Zong Ji; Cui Jin Bai; Yang Yun; Wu Xiang Dong; Qian Ze Yi; Wu Dan Ping; Tang Yi; Zheng Hong Xia; Zhang Zhi Min; Xu Jing Long; Zhang Teng Fei; Wang Jun Ji; et al. (Frontiers Media S.A., 2023)
BackgroundThe aim of this study was to examine whether academic performance is associated with students' athletic ability in primary school.MethodsA 3-year follow-up study was conducted among 1,136 Chinese students. Sit-up and jump rope testers were used to measure 1-min sit-ups and 1-min jump ropes, respectively. Meanwhile, the Pittsburgh Sleep Quality Scale and the Beck Depression Inventory were used to estimate sleep quality and depression levels. The end-of-semester examinations were used to evaluate students' academic performance during the follow-up period.ResultsAfter adjusting for confounders, the mean change in Chinese language performance for participants stratified by 1-min sit-ups at baseline was 0.35 (95% CI: −0.37 to 0.76) for level 1 (slowest), 0.52 (95% CI: −0.54 to 1.08) for level 2, and 1.72 (95% CI: 1.14 to 2.30) for level 3 (fastest) (P for trend = 0.003); the mean change in math scores was 0.28 (95% CI: −0.50 to 0.95) for level 1 (slowest), 0.95 (95% CI: 0.38 to 1.52) for level 2, and 1.41 (95% CI: 0.82 to 1.99) for level 3 (fastest) (P for trend = 0.048). The mean change in foreign language scores was −0.45 (95% CI: −0.99 to −0.93) for level 1 (slowest), −0.14 (95% CI: −0.44 to 0.41) for level 2, and 0.69 (95% CI: 0.25 to 1.13) for level 3 (fastest) (P for trend = 0.004). The mean change in Chinese language performance for participants stratified by 1-min jump ropes at the baseline was 0.30 (95% CI: −0.16 to 0.76) for level 1 (slowest), 1.09 (95% CI: 0.42 to 1.76) for level 2, and 1.74 (95% CI: 1.14 to 2.35) for level 3 (fastest) (P for trend = 0.001). The mean change in math scores was 0.41 (95% CI: −0.11 to 0.92) for level 1 (slowest), 1.44 (95% CI: 0.69 to 2.19) for level 2, and 1.43 (95% CI: 0.76 to 2.10) for level 3 (fastest) (P for trend = 0.019). The mean change in foreign language performance was −0.71 (95% CI: −1.08 to −0.33) for level 1 (slowest), 0.95 (95% CI: −0.40 to 1.50) for level 2, and 0.91 (95% CI: 0.41 to 1.41) for level 3 (fastest) (P for trend < 0.001).ConclusionThis study suggests that participation in jump rope and sit-up exercises may positively affect students' academic performance.